A Pragmatic Study of Evasion in Theresa Mays' Political Interviews - Mokhlos Faisal, Wafaa; Abid-Ali Mahdi, Wafaa (International Journal of Psychosocial Rehabilitation, 2020)
Evasion is defined as a strategy, used by politicians trying not to give direct answer or to escape from the right answer The present paper aims to study the evasion strategy in the political interviews; the study investigates evasion in Theresa May's political interviews on a pragmatic level. The present study presents a brief definition of evasion, types of evasion, which type is heavily used by May, functions that she fulfilled in her interviews, and what tactics she used to evade answering the question. This study also investigates which maxim of Grice is violated in the political interviews. The analysis consists of data on six texts of interviews with Theresa May from 2016 to 2019. The results summarize the conclusions that the study reached. Among these conclusions is that evasion has an essential role in the political interviews, and politicians tend to use it to fulfill certain functions, such as talking about special issues that lead to arguments in the media. Politicians also tend to evade answering the question in covert ways more than overt. Grice's Maxims are violated by politicians, especially relevance and manner. Politicians use several techniques in order to evade the question; diplospeak" is most widely used by them.